Respostas

2013-07-03T19:11:47-03:00

a)

 

(x+2) . (x+2) =

x²+2x+2x+4 =

x²+4x+4

 

b)

 

(2a+1) . (2a+1) =

4a²+2a+2a+1=

4a²+4a+1

 

c)

 

 (4b+1/2). (4b+1/2)

8b²+4b/2+4b/2+1/4

8b²+8b/2+1/4

 

d) ( expoentes iguais corta)

 

(4x+y).(4x+y)

8x²+4xy+4xy+y²

8x²+8xy+y²

 

 

 

2013-07-03T19:14:33-03:00

a) 

(x+2) . (x+2) =

x²+2x+2x+4 =

x²+4x+4

 

b) 

(2a+1) . (2a+1) =

4a²+2a+2a+1=

4a²+4a+1

 

c) 

 (4b+1/2). (4b+1/2)

8b²+4b/2+4b/2+1/4

8b²+8b/2+1/4

 

d)  

(4x+y).(4x+y)

8x²+4xy+4xy+y²

8x²+8xy+y²